Involvement of orexin type-2 receptors in genetic absence epilepsy rats - Toplu, Aylin; Mutlu, Nursima; Erdeve, Elif Tuğçe; Sariyildiz, Özge; Çelik, Musa; Öz-Arslan, Devrim; Akman, Özlem; Molnár, Zoltan; Çarçak, Nihan; Onat, Filiz (Frontiers in Neurology, 2023)
Introduction Orexin is a neuropeptide neurotransmitter that regulates the sleep/wake cycle produced by the lateral hypothalamus neurons. Recent studies have shown the involvement of orexin system in epilepsy. Limited data is available about the possible role of orexins in the pathophysiology of absence seizures. This study aims to understand the role of orexinergic signaling through the orexin-type 2 receptor (OX2R) in the pathophysiology of absence epilepsy. The pharmacological effect of a selective OX2R agonist, YNT-185 on spike-and-wave-discharges (SWDs) and the OX2R receptor protein levels in the cortex and thalamus in adult GAERS were investigated. Methods The effect of intracerebroventricular (ICV) (100, 300, and 600 nmol/10 μL), intrathalamic (30 and 40 nmol/500 nL), and intracortical (40 nmol/500 nL) microinjections of YNT-185 on the duration and number of spontaneous SWDs were evaluated in adult GAERS. The percentage of slow-wave sleep (SWS) and spectral characteristics of background EEG were analyzed after the ICV application of 600 nmol YNT-185. The level of OX2R expression in the somatosensory cortex and projecting thalamic nuclei of adult GAERS were examined by Western blot and compared with the non-epileptic Wistar rats. Results We showed that ICV administration of YNT-185 suppressed the cumulative duration of SWDs in GAERS compared to the saline-administered control group (p < 0.05). However, intrathalamic and intracortical microinjections of YNT-185 did not show a significant effect on SWDs. ICV microinjections of YNT-185 affect sleep states by increasing the percentage of SWS and showed a significant treatment effect on the 1–4 Hz delta frequency band power during the 1–2 h post-injection period where YNT-185 significantly decreased the SWDs. OXR2 protein levels were significantly reduced in the cortex and thalamus of GAERS when compared to Wistar rats. Conclusion This study investigated the efficacy of YNT-185 for the first time on absence epilepsy in GAERS and revealed a suppressive effect of OX2R agonist on SWDs as evidenced by the significantly reduced expression of OX2R in the cortex and thalamus. YNT-185 effect on SWDs could be attributed to its regulation of wake/sleep states. The results constitute a step toward understanding the effectiveness of orexin neuropeptides on absence seizures in GAERS and might be targeted by therapeutic intervention for absence epilepsy.